2023
DOI: 10.21037/qims-23-113
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of Kaiser score in diagnosing breast dynamic contrast-enhanced magnetic resonance imaging for patients with high-grade background parenchymal enhancement

Hui Wang,
Ling Gao,
Xu Chen
et al.

Abstract: Background High-grade background parenchymal enhancement (BPE), including moderate and marked, poses a considerable challenge for the diagnosis of breast disease due to its tendency to increase the rate of false positives and false negatives. The purpose of our study was to explore whether the Kaiser score can be used for more accurate assessment of benign and malignant lesions in high-grade BPE compared with the Breast Imaging Reporting and Data System (BI-RADS). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Suspicion of malignancy is particularly high, especially in scores exceeding 7, and patients with benign biopsy pathology results should be carefully evaluated. The Kaiser score has been reported to reduce interobserver differences and false positives 6 , 9 . Studies have demonstrated that unnecessary biopsies and surgeries can be reduced in patients with true negative results by utilizing the recommendations based on the BI-RADS classification and Kaiser score 8 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Suspicion of malignancy is particularly high, especially in scores exceeding 7, and patients with benign biopsy pathology results should be carefully evaluated. The Kaiser score has been reported to reduce interobserver differences and false positives 6 , 9 . Studies have demonstrated that unnecessary biopsies and surgeries can be reduced in patients with true negative results by utilizing the recommendations based on the BI-RADS classification and Kaiser score 8 , 10 .…”
Section: Introductionmentioning
confidence: 99%